Nucleic acids and melanin pigments after exposure to high doses of gamma rays: a biosignature robustness test. Issue 5 (6th October 2022) - Cassaro, A.; Pacelli, C.; Baqué, M.; Maturilli, A.; Boettger, U.; Moeller, R.; Fujimori, A.; de Vera, J-P.P.; Onofri, S.
Abstract: The question about the stability of certain biomolecules is directly connected to the life-detection missions aiming to search for past or present life beyond Earth. The extreme conditions experienced on extraterrestrial planet surface ( e.g. Mars), characterized by ionizing and non-ionizing radiation, CO2 -atmosphere and reactive species, may destroy the hypothetical traces of life. In this context, the study of the biomolecules behaviour after ionizing radiation exposure could provide support for the onboard instrumentation and data interpretation of the life exploration missions on other planets. Here, as a part of STARLIFE campaign, we investigated the effects of gamma rays on two classes of fungal biomolecules–nucleic acids and melanin pigments – considered as promising biosignatures to search for during the ' in situ life-detection' missions beyond Earth.